2022
DOI: 10.1007/s11302-022-09883-1
|View full text |Cite|
|
Sign up to set email alerts
|

Adenosine receptor signalling in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is the most common dementia in the elderly and its increasing prevalence presents treatment challenges. Despite a better understanding of the disease, the current mainstay of treatment cannot modify pathogenesis or effectively address the associated cognitive and memory deficits. Emerging evidence suggests adenosine G protein-coupled receptors (GPCRs) are promising therapeutic targets for Alzheimer’s disease. The adenosine A1 and A2A receptors are expressed in the human brain and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 305 publications
0
5
0
Order By: Relevance
“…Adora3 encodes a G-protein coupled adenosine receptor type 3, which is supposed to mediate inhibition of neutrophil degranulation and therefore potentially prevents cell damage. However, it was also reported to exhibit ambiguous effects in neuroprotection and neurodegeneration [ 108 , 148 , 149 ] stressing that modulation of the adenosinergic system in AD, in terms of pathology and therapeutics, is a sophisticated issue [ 150 ]. Despite this potential intractability and the lack of medicines targeting adenosinergic receptors for AD treatment, substantial efforts are made in drug research and development.…”
Section: Discussionmentioning
confidence: 99%
“…Adora3 encodes a G-protein coupled adenosine receptor type 3, which is supposed to mediate inhibition of neutrophil degranulation and therefore potentially prevents cell damage. However, it was also reported to exhibit ambiguous effects in neuroprotection and neurodegeneration [ 108 , 148 , 149 ] stressing that modulation of the adenosinergic system in AD, in terms of pathology and therapeutics, is a sophisticated issue [ 150 ]. Despite this potential intractability and the lack of medicines targeting adenosinergic receptors for AD treatment, substantial efforts are made in drug research and development.…”
Section: Discussionmentioning
confidence: 99%
“…Another work in which the A 2A R was removed from THY-Tau22 mice found that silencing A 2A R protects the mice against tau-pathology-induced deficiencies in spatial memory and long-term hippocampal depression [ 86 ]. Overall, the findings suggest a contribution of A 2A R to the pathogenesis of AD [ 87 , 88 ].…”
Section: A 2a Adenosine Receptors In Admentioning
confidence: 99%
“…P2Y12R is a member of the purinergic signaling family ( Dahlquist and Diamant, 1974 ; Hynie, 1995 ; Burnstock, 2004 ; Burnstock, 2007 ). Purinergic signaling, which includes nucleotides (e.g., adenosine triphosphate (ATP)), their hydrolysis products (adenosine diphosphate (ADP), adenosine monophosphate (AMP)), nucleosides (e.g., adenosine), enzymes (CD39, CD73) and purinergic p ) receptors, was proposed by Burnstock in 1972 and has been recognized as a new etiological factor or promising potential target for the treatment of central nervous system disorders ( Huang et al, 2021 ; Li et al, 2022 ; Trinh et al, 2022 ; Iring et al, 2021 ; Ribeiro et al, 2022 ). The binding of extracellular nucleosides and nucleosides to purinergic receptors leads to the activation of intracellular signaling pathways, which in turn gives rise to changes in cell physiology ( Zimmermann, 2006 ; Burnstock, 2008 ; Burnstock, 2018 ; Burnstock, 2020 ).…”
Section: Potential Therapeutic Value Of P2y12rmentioning
confidence: 99%